Measles seroprevalence in Thailand: are adolescents and young adults at risk of measles? - Panit Takkinsatian; Kamolmart Wannaphahoon; Prasit Upapan; Sansnee Senawong; Olarn Prommalikit (Singapore Medical Journal)
Introduction: During the last decade, measles has become an important re-emerging disease in Thailand. The objective of this study was to measure measles seroprevalence and its influencing factors so as to plan an improved vaccination programme. Methods: A total of 600 participants aged between 9 months and 50 years were divided into seven groups representing birth cohorts that experienced different measles vaccination policies. Participants’ blood samples were obtained to measure measles immunoglobulin G (IgG) levels. Results: None of the participants in the age group of 9 months had measles IgG levels beyond a protective level. Participants in the age groups 2.5, 5–15, 16–29, 30–33, 34–40 and 41–50 years had 82% (95% confidence interval [CI] 73.3–90.7), 50% (95% CI 36.1–63.9), 52% (95% CI 42.3–62.7), 70% (95% CI 61.1–78.9), 88.8% (95% CI 84.1–93.5) and 98.8% (95% CI 96.4–100.0) measles seropositivity, respectively. The study did not find any significant factors affecting measles seropositivity. Conclusion: Individuals aged 15–34 years are vulnerable to measles infections. Supplementary vaccination should be encouraged in special situations, including postexposure prophylaxis for young adults during an outbreak and for high-risk occupations such as healthcare personnel.